PENILAIAN SAHAM PT PLAZA INDONESIA REALTY Tbk. DALAM RANGKA PENJUALAN ASET ANAK PERUSAHAAN PER TANGGAL 30 SEPTEMBER 2010 - , Totok Wasito, S.T. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to estimate the intrinsic value of the shares of PT Plaza Indonesia Realty Tbk. relating to the sale of assets of a subsidiary of PT Plaza Nusantara Realti by using the income approach is to apply the discounted cash flow method and the market data comparison approach (relative valuation). The data used consists of financial statements data PT Plaza Indonesia Realty Tbk. during the last five years from 2005 to 2009 and limited review of financial statements as of 30 September 2010. Analysis of discounted cash flow method conducted by: an analysis of sales or earnings projections, projections of financial statements, the projected free cash flow, the determination of the discount rate or the level of feed back is expected and the estimated value. Analysis of the market data comparison approach (relative valuation) begins with finding comparable companies in similar lines of business subsequent to choose and assign the appropriate multiples or ratios of comparable companies. Multiples are used to convert the book value of relevant variables from the PT Plaza Indonesia Realty Tbk. be the estimated market value. Multiplesor ratios used are: PER (Price Earning Ratio), PBV (Price to Book Value) and P / S (Price to Sales Ratio). The results of both approaches, obtained estimates of the intrinsic value of the shares of PT Plaza Indonesia Realty Tbk per 30 September 2010 per share before /without asset sales subsidiaries ranges from Rp984,- up to Rp1,000,- with an average value of the stockper share of Rp992,-. Estimates of the intrinsic value of the shares of PT Plaza Indonesia Realty Tbk per 30 September 2010 per share after the sale of assets between subsidiaries Rp1.500,- up to Rp1.518,- with an average value of the stock per share of Rp. 1509,-. Value of the shares of PT Plaza Indonesia Realty Tbk. and financial ratios after the sale of subsidiary assets increased when compared to the value of financial ratios before/ without asset sales subsidiary, the subsidiary making the sale of assets is the right choice by management and safe for the shareholders.